Payroll Accounting System of Lecturers At Politeknik Harapan Bersama - Ghea Dwi Rahmadiane (JPA : Journal of Public Accounting, 2021)
In carrying out its company operations, companies need to develop an adequate system and procedure so that all company activities can run smoothly. In providing salaries or wages, companies may not give salaries or wages arbitrarily, because salaries or wages are a form of company appreciation for all employee contributions to the company for the work that has been done, the amount of income received by the employee, the minimum must follow the laws and government regulations that regulate wages that are adjusted in each region in the form of the Minimum Wage. This study aims to determine the salary information system for lecturers at Politeknik Harapan Bersama. This study uses primary data in the form of interviews with the Head of Finance and Head of Personnel at Politeknik Harapan Bersama and uses secondary data in the form of organizational structure and payroll system flowcharts. The analytical technique used in this study is qualitative analysis which underlies theory of Mulyadi (2001). The results of this study can be said that the payroll information system at the Harapan Bersama Polytechnic is in accordance with the theory of Mulyadi (2001) with the compatibility between the functions involved in the system, the documents used, internal controls, accounting records, and flowcharts on the payroll system for the lecturers of Politeknik Harapan Bersama. The Accounting Section which controls the lecturers' payroll process is still in the Finance Department, therefore it is recommended that the Accounting Section become an independent section in order to have better policies in the process of controlling the payroll system for Politeknik Harapan Bersama lecturers.